Politeness Lost in Translation? A Linguistic Study of Impolite Twitter Reactions on Bloomberg’s G20 Summit Post - Safitri, Hilma; Putri , Astari Amalia; Sari, Dwi Erika (Universitas Lancang Kuning, 2025)
In the era of digital globalization, online discourse often becomes a battleground of competing ideologies, emotions, and linguistic behaviors, particularly on platforms like Twitter, now known as X. This study explores the intersection of impoliteness strategies and annotated translation techniques by analyzing forty selected user comments responding to Bloomberg’s posts about the 2022 G20 Summit in Bali, Indonesia. These comments, perceived as inappropriate or impolite, reflect not only socio-political tensions but also the complex challenges of preserving communicative intent in translation. Employing a qualitative design grounded in Culpeper’s impoliteness framework and Molina and Albir’s taxonomy of translation techniques, the study identifies three dominant impoliteness purposes: entertainment (57.5%), affective (32.5%), and coercive (10%), alongside five translation techniques including compensation, variation, modulation, literal, and transposition. A key finding reveals that the translation techniques used did not always align directly with the original communicative purpose, highlighting the translator’s interpretive agency. This research addresses a significant gap in translation studies by focusing on the nuanced function of impolite language in digital public discourse and how translation reshapes or mediates its effect. By situating translation within the dynamics of sociocultural offense and affective expression, the study contributes to a richer understanding of pragmatics in multilingual media contexts. It provides practical implications for translation practitioners, educators, and discourse analysts concerned with linguistic fidelity, cultural sensitivity, and communicative efficacy in cross-cultural digital environments.